Bezeichnungen für Menschen mit Behinderungen in polnischen und tschechischen Presseberichten über die Paralympics 2014 in Soči. Terms denoting people with disabilities in Polish and Czech press reports about the Paralympic Games in Sochi in 2014. - Radünzel, Claudia (Glottodidactica, 2016)
The present article deals with Polish and Czech terms that denote people with disabilities placing a particular focus on the structure of these terms and the frequency of their use in current language. The study is based on articles about the XI Paralympic Winter Games in Sochi published in the online issues of Polish and Czech newspapers from March 2014. The texts show a tendency to use alternate, euphemistic terms instead of the more established ones.